An unexpected diagnosis of a lung mass with endobronchial involvement - Köhl, Johanna; Bardaro, Floriana; Stirpe, Emanuele (Monaldi Archives for Chest Disease, 2022)
Mantle cell lymphoma is a subtype of B-cell non-Hodgkin’s lymphoma. Most cases of the disease have extranodal involvement at the time of the initial diagnosis; however, endobronchial involvement is rare. A 51-year-old woman was referred to our hospital because a chest CT showed pathological tissue in the right hilum englobing the pulmonary artery, the left main bronchus and their main lobar branches appearing to be small in caliber, multiple lymphadenopathies up to 4 cm in size in the subcarinal region. A bronchoscopy revealed stenotic lumen with infiltrated hyperemic mucosa of the left upper lobar bronchus and the left lower lobar bronchus. She was diagnosed as having mantle cell lymphoma based on an endobronchial biopsy and transbronchial needle aspiration. The diagnosis was confirmed using immunohistochemical staining.